Generic classification of the Archiborborinae (Diptera: Sphaeroceridae), with a revision of Antrops Enderlein, Coloantrops gen. nov., Maculantrops gen. nov., Photoantrops gen. nov., and Poecilantrops gen. nov. - Kits, Joel H.; Marshall, Stephen A. (Zootaxa, 2013)
The Archiborborinae comprise a diverse clade of flies in the family Sphaeroceridae. We here revise the generic classification, redefining the genus Antrops Enderlein and naming 5 new genera: Boreantrops gen. nov., Coloantrops gen. nov., Maculantrops gen. nov., Photoantrops gen. nov., and Poecilantrops gen. nov. The genus Archiborborus, until recently a paraphyletic assemblage including most of the described species in the subfamily, is treated as a junior synonym of Antrops (syn. nov.) We revise the genera Antrops (53 species, including 40 sp. nov.: Antrops anovariegatus, Antrops aurantifemur, Antrops baeza, Antrops bellavista, Antrops biflavus, Antrops bucki, Antrops carpishensis, Antrops cochabamba, Antrops cochinoca, Antrops coniobaptos, Antrops coroico, Antrops cotopaxi, Antrops didactylos, Antrops diversipennis, Antrops eurus, Antrops fulgiceps, Antrops fuliginosus, Antrops guandera, Antrops guaramacalensis, Antrops inca, Antrops juninensis, Antrops mucarensis, Antrops niger, Antrops papallacta, Antrops pecki, Antrops podocarpus, Antrops quadrilobus, Antrops siberia, Antrops sierrazulensis, Antrops tachira, Antrops tequendama, Antrops tetrastichus, Antrops tumbrensis, Antrops unduavi, Antrops variegatus, Antrops versabilis, Antrops vittatus, Antrops yungas, and Antrops zongo and the following comb. nov.: Antrops annulatus (Richards), Antrops chaetosus (Richards), Antrops femoralis (Blanchard), Antrops hirtus (Bigot), Antrops maculipennis (Duda), Antrops maximus (Richards), Antrops microphthalmus (Richards), Antrops quadrinotus (Bigot), Antrops setosus (Duda), Antrops simplicimanus (Richards), Antrops nitidicollis (Becker), and Antrops orbitalis (Duda)), Coloantrops (1 species: Coloantrops daedalus, sp. nov.), Maculantrops (2 species, Maculantrops hirtipes (Macquart) comb. nov. and Maculantrops altiplanus, sp. nov.), Photoantrops (1 species: Photoantrops echinus sp. nov.), and Poecilantrops (10 species: Poecilantrops baorucensis, Poecilantrops boraceiensis, Poecilantrops crocidosternum, Poecilantrops dominicus, Poecilantrops flavifemur, Poecilantrops marensis, Poecilantrops plaumanni, Poecilantrops psilosternum, Poecilantrops stellans, Poecilantrops vittifrons, all sp. nov.). Six additional species of Antrops and two of Poecilantrops known from females only are diagnosed but not described. The genus Boreantrops is described for two species (Boreantrops mexicanus (Steyskal) comb. nov., and Boreantrops calceatus (Duda) comb. nov.). Boreantrops includes a number of new species but is not fully revised here. New synonyms at the species level are: Antrops femoralis (Blanchard 1852) = Archiborborus argentinensis Papp 1977, and Archiborborus submaculatus Duda 1921, both syn. nov.; Antrops hirtus (Bigot 1888) = Archiborborus edwardsi Richards 1931, syn. nov.; Antrops quadrinotus (Bigot 1888) = Archiborborus albicans Richards 1931, Archiborborus chilensis Richards 1931, Archiborborus koenigi Duda 1932, all syn. nov.; Maculantrops hirtipes (Macquart 1844) = Copromyza alternata Rondani 1868, syn. nov.